PENERAPAN AKUNTANSI SYARIAH PADA LEMBAGA KEUANGAN NON PERBANKAN DI KOTA PONTIANAK - Kristiawati, Endang (Program Studi Akuntansi Universitas Panca Bhakti, 2021)
This research was carried out at non-banking financial intitutions in the city of Pontianak namely Koperasi Simpan Pinjam dan Pembiayaan Syariah (KSPPS) Kal-Bar Madani and Koperasi Serba Usaha (KSU) Baitul Maal wa Tamwil (BMT) Mujahidin Pontianak with title “ Analysis of Aplication Sharia Accounting At Non-Banking Financial Intitutions In Pontianak City “. The purpose of this research is to know the application of Islamic Financial Accounting Standards to KSPPS Kal-Bar Madani and KSU BMT Mujahidin. The method used qualitative descriptive method with data collection technique through literature study, observation, interview, document. The analytical tool used for this research is Islamic Financial Accounting Standards namely PSAK 101, PSAK 102, and PSAK 105.The results show that the recording, recognition, and measurement, presentation, disclosure and financial reporting by KSPPS Kal-Bar Madani have not been in accordance with the Islamic Financial Accounting Standards that should be, while KSU BMT Mujahidin has applied part of Islamic Financial Accounting Standards. Keywords: SAK, Union, Sharia